Fusion crust in ordinary chondrites: a study from nature to the experiments - Pittarello, Lidia; Goderis, Steven; Soens, Bastien; McKibbin, Seann J.; Bariselli, Federico; Barros Dias, Bruno R.; Helber, Bernd; Giuli, Gabriele; Lepore, Giovanni O.; Yamaguchi, Akira; Roszjar, Julia; Debaille, Vinciane; et al. (2018)
The Ninth Symposium on Polar Science/Ordinary sessions: [OA] Antarctic meteorites / Hayabusa, Wed. 5 Dec. / Conference hall of the Research/Administration Building (2nd floor) at the JAXA Sagamihara Campus conference object